Detail Guide for Cfd on the Simulation of Biogas Combustion in Bluff-Body Mild Burner - M. M., Noor; Andrew P., Wandel; Talal, Yusaf (2013)
Combustion is still the most important process to generate energy. The improvement of combustion efficiency will give high impact to the cost of energy. Beside experimental testing, computational work nowadays becoming more and more important due to lower cost and acceptable accuracy with minimum error. Especially for new develop model, the computational testing using Computational Fluid Dynamics (CFD) software will reduce a lot of trial and error on experimental work. The detail of CFD step by step was focus for this paper for the biogas MILD combustion bluff-body burner. The simulation was carryout using ANSYS 14.5. The ANSYS Modeller was used to model the burner and ANSYS Meshing was used to mesh the model. Finally the Fluent was used to calculate the solution. The post processing was carryout using CFD-Post. The non- premixed combustion with turbulent realizable k-epsilon was used in the simulation and produce MILD combustion in the combustion chamber.